Hubungan Kemampuan Literasi Digital Dengan Pemanfaatan E-Library Siswa SMA Negeri 1 Bukittinggi - Muhammad Marzuki; Yona Primadesi (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to describe how e-libraries benefit from digital literacy. This research uses quantitative research with descriptive methods. The population in this study were students of SMA Negeri 1 Bukittinggi with a sample of 93 respondents. The sampling technique in this research used random sampling technique. The instrument of this research is a questionnaire as the main data. Apart from that, data collection techniques are carried out through observation and documentation. To find out the correlation value between variable X and variable Y, the Product Moment correlation formula from Karl Pearson is used with the help of the SPSS application program. The results of this research show firstly, students of SMAN 1 Bukittnggi use E-library to search for reference materials. Second, students of SMAN 1 Bukittnggi understand how to use the E-library by utilizing the features provided by the E-library. Third, students of SMAN 1 Bukittnggi utilize the features provided by the E-library to search for information. Fourth, all types of information available on the E-library can be accessed freely by students of SMAN 1 Bukittnggi. The correlation test uses the Pearson formula with the help of the SPSS version 23 application program, which produces a correlation coefficient of 0.323. So it can be concluded that the correlation value of digital literacy skills with students' use of e-libraries is in the medium category. Hypothesis testing results show Fcount > Ftable, which means the alternative hypothesis Ha is accepted while H0 is rejected. So from this analysis it can be concluded that there is a significant relationship between digital literacy skills (variable X) and the use of e-libraries (variable Y) by students at SMA Negeri 1 Bukittinggi. Based on testing the coefficient of determination through a simple linear regression test, it has a value of 10.5%, this shows that the influence of digital literacy skills on e-library use is 10.5% and the remaining 89.5% is influenced by other factors.